A simplified method for the efficient purification and refolding of recombinant human TRAIL. (11th May 2020) - Zhang, Zhenjiang; Hahn, Su Bin; Cao, Thong M.; King, Michael R.
Abstract: Tumor necrosis factor (TNF)‐related apoptosis‐inducing ligand (TRAIL) belongs to the TNF cytokine superfamily that specifically induces apoptosis in a broad spectrum of human cancer cell lines but not in most healthy cells. The antitumor potential of recombinant human TRAIL (rhTRAIL) has attracted great attention among biologists and oncologists. However, attempts to express rhTRAIL in Escherichia coli often results in limited yield of bioactive protein due to the formation of inclusion bodies (IBs), which are dense insoluble particulate protein aggregates inside cells. We describe herein a highly simplified method to produce pure bioactive rhTRAIL using E. coli . The method is straightforward and requires only basic laboratory equipment, with highly efficient purification and high yield of renaturation, and may also be applied to produce other proteins that form IBs in E. coli .